Pengembangan Bahan Ajar Teks Deskripsi Berbasis Aplikasi Android Construct 2 Kelas VII SMP/MTS - Vinnisya, Alya; Utami, Sintowati Rini; Murtadho, Fathiaty (Bastrando: Jurnal Bahasa dan Sastra Indonesia, 2024)
This research aims to develop descriptive text teaching materials based on the Android Construct 2 application. Based on analysis data, teaching materials are developed using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model in Research and Development research. Teaching materials begin with analysis which includes curriculum analysis, teaching materials, student needs, and teacher interviews. The results of the analysis of student needs show that students have studied and know the basic descriptive text material, but the structure and needs material is material that is still difficult to understand. Based on the results of the analysis, a research design was prepared including curriculum design, materials, and media. Based on the design results, a research development was prepared including the cover of the teaching materials, the introductory part included a menu for getting to know the material, games, and evaluation, learning activity part 1 presented learning using a scientific approach, learning activity 2 presented descriptive text material, and learning activity 3 presented the game menu. Based on the development results, the product was implemented in the form of product confirmation to teachers with the result of getting a tick in the "YES" column in all aspects and confirmation from class VII students at SMP NEGERI 74 Jakarta by getting a "YES" tick for a total of thirty-one out of thirty-two aspects. Based on this, it can be concluded that the product that has been developed is suitable for use in the learning process.